2021
DOI: 10.21203/rs.3.rs-122455/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

mTOR inhibitor improves autistic-like behaviors related to Tsc2 haploinsufficiency but not following developmental status epilepticus

Abstract: Background: Tuberous Sclerosis Complex (TSC), a multi-system genetic disorder often associated with Autism Spectrum Disorder (ASD), is caused by mutations of TSC1 or TSC2, which lead to constitutive overactivation of mammalian Target of Rapamycin (mTOR). In several Tsc1+/- and Tsc2+/- animal models, cognitive and social behavior deficits were reversed by mTOR inhibitors. However, phase II studies have not shown amelioration of ASD and cognitive deficits in individuals with TSC during mTOR inhibitor therapy. We… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 69 publications
(124 reference statements)
0
4
0
Order By: Relevance
“…Petrasek and co‐workers recently reported a deficit of anogenital social exploration in Eker rats from the same breeding colony (Petrasek et al, 2021). The discrepancy between the results of the previous study with the current report can perhaps be explained by the fact that the rats in this study (both genotypes) generally were socially less active (compare Figure 2b, c in Petrasek et al, 2021, with Figure 3a, b in the present study), seemingly contributed by differences in housing conditions. Also, the earlier studies used non‐IVC cages, with cage type known to influence rat performance in behavioural tests (Brain & Benton, 1979; Van de Weerd et al, 2002; Wurbel, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Petrasek and co‐workers recently reported a deficit of anogenital social exploration in Eker rats from the same breeding colony (Petrasek et al, 2021). The discrepancy between the results of the previous study with the current report can perhaps be explained by the fact that the rats in this study (both genotypes) generally were socially less active (compare Figure 2b, c in Petrasek et al, 2021, with Figure 3a, b in the present study), seemingly contributed by differences in housing conditions. Also, the earlier studies used non‐IVC cages, with cage type known to influence rat performance in behavioural tests (Brain & Benton, 1979; Van de Weerd et al, 2002; Wurbel, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Waltereit et al showed a reduction in social interactions in rats after induction of status epilepticus at a very young age (Waltereit et al, 2011). Petrasek and co‐workers recently reported a deficit of anogenital social exploration in Eker rats from the same breeding colony (Petrasek et al, 2021). The discrepancy between the results of the previous study with the current report can perhaps be explained by the fact that the rats in this study (both genotypes) generally were socially less active (compare Figure 2b, c in Petrasek et al, 2021, with Figure 3a, b in the present study), seemingly contributed by differences in housing conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations